Potential of green banana as biodegradable packaging films - Zainal Abidin, Nur Hanani; Jasny, Nur Raihani; Abdul Halim, Nurhasmilaalisa (2014)
This study investigated the properties of green banana films as potential packaging films. Banana films from green banana (with concentrations 2-10% w/w) were prepared by using casting method. This study investigated the properties of green banana films as potential packaging films. Banana films from green banana (with concentrations 2-10% w/w) were prepared by using casting method. The mechanical properties (tensile strength (TS), elongation at break (EAB) and Young’s modulus), water vapor permeability (WVP), and solubility of films were determined. TS and Young’s modulus of banana films improved (P < 0.05) when the concentration of banana increased. However, WVP of the films inreased (P < 0.05) when the concentration increased from 2-6% with solubility of films decreased (P < 0.05). Concentration of banana used gave affect to the mechanical and barrier properties of films obtained.